Molecular behavior of human Mrt4 protein, MRTO4, in stress conditions is regulated by its C-terminal region. (December 2015) - Michalec-Wawiorka, Barbara; Wawiorka, Leszek; Derylo, Kamil; Krokowski, Dawid; Boguszewska, Aleksandra; Molestak, Eliza; Szajwaj, Monika; Tchorzewski, Marek
Highlights: Human Mrt4 protein is phosphorylated in vivo . Three serines within C-termini of hMrt4/MRTO4 are phosphorylated by CK2 in vitro . hMrt4/MRTO4 phosphorylation/dephosphorylation equilibrium determines its behavior during nucleolar stress induced by ActD treatment. Abstract: Protein Mrt4 is one of trans -acting factors involved in ribosome biogenesis, which in higher eukaryotic cells contains a C-terminal extension similar to the C-terminal part of ribosomal P proteins. We show that human Mrt4 (hMrt4/MRTO4) undergoes phosphorylation in vivo and that serines S229, S233, and S235, placed within its acidic C-termini, have been phosphorylated by CK2 kinase in vitro . Such modification does not alter the subcellular distribution of hMrt4 in standard conditions but affects its molecular behavior during ActD induced nucleolar stress. Thus, we propose a new regulatory element important for the stress response pathway connecting ribosome biogenesis with cellular metabolism.